Simultaneous and proportional control of 2D wrist movements with myoelectric signals - Hahne, J. M.; Rehbaum, H.; Biessmann, F.; Meinecke, F. C.; Muller, K.; Jiang, N.; Farina, D.; Parra, L. C. (2012 IEEE International Workshop on Machine Learning for Signal Processing, 2012)
Previous approaches for extracting real-time proportional control information simultaneously for multiple degree of Freedom(DoF) from the electromyogram (EMG) often used non-linear methods such as the multilayer perceptron (MLP). In this pilot study we show that robust control is also possible with conventional linear regression if EMG power measures are available for a large number of electrodes. In particular, we show that it is possible to linearize the problem with simple nonlinear transformations of band-pass power. Because of its simplicity the method scales well to high dimensions, is easily regularized when insufficient training data is available, and is particularly well suited for real-time control as well as on-line optimization.